AB1441-HPR Does the incidence of infections increase in patients with chronic arthritis and osteoporosis treated with denosumab and biological therapy?. (12th June 2018) - Lopez Esteban, A; Garcia, F.; Janta, I.; Ovalles, J.G.; Serrano, B.; Sanchez, J.C.; Garaballu, C.; Gonzalez, C.; Del Rio, T.; Lopez Longo, J.; Gonzalez, C.; Monteagudo, I.; et al.
Abstract : Background: Biological therapies (BT) have changed the prognosis of chronic arthritis (CA); however, they have associated the increased risk of infections. Denosumab (DNS) is the first biologic approved for the treatment of osteoporosis (OP) and is also associated with an increased risk of infections. Objectives: To evaluate the incidence of infections in patients with CA and OP treated with DNS alone or associated to another biological treatment. Methods: A prospective observational study was designed in which all patients with OP who received treatment with DNS between January 2013 and December 2017 were included. The group of patients with CA (RA, EA, PsA) were treated, in addition to DNS as treatment for their OP, with BT. Follow-up was carried out in the rheumatology nursing examination room every 6 months. Demographic data, disease charaacteristics, infections and associated comorbidities were collected. Serious infections were defined as those that required admission, suspension of therapy or death. Results: 220 patients were included (81.1% women). The main diagnoses were OP 112 (51%) and AC 76 (34.5%) [RA 58 patients (26.3%), SpA 8 (3.6%), Psa 10 (4.5%)] and other rheumatologic diagnoses 32 (14.5%). Demographic data are shown in Table 1. Both groups were similar except for the higher GC consumption and the higher lumbar bone mass of the CA group. Of the patients with CA, 41 patients received a synthetic DMARD (MTXmainly, 90%), and 40 patients (53.9%) received GC. The average dose of DNS injections was 4.5 (1–10), with average treatment duration (range and DS) of 23.03 months (6–66, 13.3).The incidence of infections was 74 (39.3%), 31 patients had repeated infections. The most frequent were urinary tract infections (UTI), respiratory, mouth and other infections. There were 4 serious infections, 2 UTI and 2 pneumonias (both concluded in death, in patients with RA). The incidence of infections among patients with OP and with CA was similar in both groups (40 (35.7%) vs. 34 (44.7%), p<0.209). Multiple regression including age, synthetic DMARD, GC and duration of treatment with DNS showed that the duration of treatment with DNS [Exp (B=1.058, p<0.001] and GC [Exp (B)=2.484, p=0.010] were the only predictors of increased risk of infections. Conclusions: Patients with CA and OP who receive DNS and TB have a similar incidence of infections. However, the risk of infection is higher in CA patients related with the use of GC. The most frequent infection was UTI followed by respiratory infections, but they did not suppose the suspension of the treatment in the majority of the cases. Disclosure of Interest: None declared